(untitled) (Economics and region, 2017)
UDC 336.5.02 Svystun, PhD (Economics). R. Levkova, master student. Poltava National Technical Yurii Kondratyuk University. Improvement of the enterprise cost management system under the conditions of an unstable economy. The article substantiates the necessity of transforming the cost management system at the enterprise in the current conditions of management, in particular, the crisis phenomena in the economy. The main methods of cost management were presented, their advantages and disadvantages were analyzed. In article the authors proposed to use the cost management method at the enterprise "Just-in-Time" as the most expedient in the conditions of an unstable external economic environment. Measures to improve the system of cost management at the enterprise and to optimize their level were proposed. Keywords: costs, cost management system, cost management methods, the economic crisis.